2020
DOI: 10.1111/irel.12255
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants and Workplace Training: Evidence from Canadian Linked Employer–Employee Data

Abstract: Job training is one of the most important aspects of skill formation and human capital accumulation. In this study, we use longitudinal Canadian linked employer–employee data to examine whether white/visible minority immigrants and Canadian‐born emplooyees experience different opportunities in two well‐defined measures of firm‐sponsored training: on‐the‐job training and classroom training. While we find no differences in on‐the‐job training between different groups, our results suggest that visible minority im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…For example, a study that experimentally changed the race/ethnicity of an employee in a photo while asking study participants to evaluate their performance demonstrated that simple acts such as being late for work led to a significantly greater negative impact on the appraisal of hypothetical employees when the photo showed a Black or Latinx employee than when the photo showed a white employee (Luksyte et al, 2013). Visible minorities are also less likely to receive training opportunities that can influence upward mobility in the labor force (Dostie and Javdani, 2020).…”
Section: Discrimination In Promotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study that experimentally changed the race/ethnicity of an employee in a photo while asking study participants to evaluate their performance demonstrated that simple acts such as being late for work led to a significantly greater negative impact on the appraisal of hypothetical employees when the photo showed a Black or Latinx employee than when the photo showed a white employee (Luksyte et al, 2013). Visible minorities are also less likely to receive training opportunities that can influence upward mobility in the labor force (Dostie and Javdani, 2020).…”
Section: Discrimination In Promotionsmentioning
confidence: 99%
“…, 2013). Visible minorities are also less likely to receive training opportunities that can influence upward mobility in the labor force (Dostie and Javdani, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Opportunity requires that all people are provided opportunities to fulfil their potential through participation (Ballen et al, 2019;Clark, 2022), when applying for jobs and promotions (Crown et al, 2020;Dostie & Javdani, 2020;Russen et al, 2021), and in education, training, and development (Brown et al, 2022;Cech & Waidzunas, 2021;Sisco, 2020).…”
Section: A Proposed Framework To Address the Needs Of All Peoplementioning
confidence: 99%
“…In so doing, this paper also brings together and contributes to two strands of literature: First, to the literature on skill obsolescence and second to the literature on benefits of lifelong learning. While the literature on lifelong learning finds that training measures on average have positive effects on productivity and labor market outcomes (Carruthers & Sanford, 2018; Frazis & Loewenstein, 2005; Georgiadis & Pitelis, 2016; Jacobson et al, 2005; Konings & Vanormelingen, 2014), studies of that literature also find that these returns are very heterogeneous depending on educational levels and individual worker characteristics (Coelli & Tabasso, 2019; Dostie & Javdani, 2020; Gauly & Lechner, 2019; Leuven & Oosterbeek, 2008; Schwerdt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%